Late anastomotic complication after laparoscopic surgery for clinical stage I low rectal cancers located within 5 cm of the anal verge: Sub‐analysis of the ultimate trial - Manabu Shimomura; Masanori Yoshimitsu; Yuichiro Tsukada; Hideki Ohdan; Jun Watanabe; Yosuke Fukunaga; Yasumitsu Hirano; Kazuhiro Sakamoto; Hiroki Hamamoto; Hisanaga Horie; Nobuhisa Matsuhashi; Yoshiaki Kuriu; et al. (Annals of Gastroenterological Surgery, 2025)
Abstract Background Although extensive research has been conducted on early anastomotic leakage (AL) after sphincter‐sparing surgery, the status of late anastomotic complications (post‐30 days) has received limited attention. These late complications significantly affect a patient's quality of life and often lead to permanent stoma creation. Methods This study conducted a sub‐analysis of a phase II trial assessing the outcomes of laparoscopic surgery for cStage I lower rectal adenocarcinoma (the ultimate trial). This study included 278 patients who underwent intestinal anastomosis and investigated the frequency, timing, and risk factors of late anastomotic complications (stenosis, fistula, and intestinal prolapse). Results Anastomotic stenosis occurred in 27 patients (9.7%), and the median time of occurrence was 274 days (range, 70–1226 days). Only early AL (p = 0.004) was identified as an independent risk factor. A late anastomotic fistula was observed in five patients (1.8%), and 18 patients (6.4%) requiring permanent stomas. A short distance from the lower tumor margin to the anal verge (AV) (p = 0.004) and the presence of stenosis or fistula (p < 0.0001) were independent risk factors. Intestinal prolapse occurred in eight cases (3%), with a median occurrence of 221 days (range, 122–725 days). Intersphincteric resection (ISR) (p = 0.02) and splenic flexure takedown (p < 0.0001) were independent risk factors. Conclusion Anastomotic stenosis and late fistula formation frequently emerge as secondary consequences of early AL and represent significant complications linked to permanent stoma creation, often proving resistant to treatment. Intestinal prolapse is a characteristic anastomotic complication of ISR that can be caused by excessive intestinal mobilization.